Reconsidering Bank Capital Regulation : A New Combination of Rules, Regulators, and Market Discipline - Fullenkamp, Connel; Rochon, Celine (Washington, D.C. : International Monetary Fund, 2014)
Despite revisions to bank capital standards, fundamental shortcomings remain: the rules for setting capital requirements need to be simpler, and resolution should be an essential part of the capital requirement framework.We propose a new system of capital regulation that addresses these needs by making changes to all three pillars of bank regulation: only common equity should be recognized as capital for regulatory purposes, and risk weighting of assets should be abandoned; capital requirements should be assigned on an institution-by-institution basis according to a regulatory (s,S) approach developed in the paper; a standard for prompt, corrective action is incorporated into the (s,S) approach.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet